Risk of chronic pancreatitis in carriers of loss-of-function CTRC variants: A meta-analysis. - Amanda Takáts; Gergő Berke; Noémi Gede; Balázs Csaba Németh; Heiko Witt; Stanisław Głuszek; Agnieszka Magdalena Rygiel; Péter Hegyi; Miklós Sahin-Tóth; Eszter Hegyi (PLoS ONE, 2022)
The digestive protease chymotrypsin C (CTRC) protects the pancreas against pancreatitis by degrading potentially harmful trypsinogen. Loss-of-function genetic variants in CTRC increase risk for chronic pancreatitis (CP) with variable effect size, as judged by the reported odds ratio (OR) values. Here, we performed a meta-analysis of published studies on four variants that alter the CTRC amino-acid sequence, are clinically relatively common (global carrier frequency in CP >1%), reproducibly showed association with CP and their loss of function phenotype was verified experimentally. We found strong enrichment of CTRC variants p.A73T, p.V235I, p.K247_R254del, and p.R245W in CP cases versus controls, yielding OR values of 6.5 (95% confidence interval (CI) 2.4-17.8), 4.5 (CI 2.2-9.1), 5.4 (CI 2.6-11.0), and 2.6 (CI 1.6-4.2), respectively. Subgroup analysis demonstrated disease association of variants p.K247_R254del and p.R245W in alcoholic CP with similar effect sizes as seen in the overall CP group. Homozygosity or compound heterozygosity were rare and seemed to be associated with higher risk. We also identified a so far unreported linkage disequilibrium between variant p.K247_R254del and the common c.180C>T (p.G60 =) haplotype. Taken together, the results indicate that heterozygous loss-of-function CTRC variants increase the risk for CP approximately 3-7-fold. This meta-analysis confirms the clinical significance of CTRC variants and provides further justification for the genetic screening of CP patients.